ASSOCIATION OF SUBCHORIONIC HEMATOMA WITH PRETERM LABOUR IN PATIENTS WITH THREATENED ABORTION - Khan, Rakhshanda Inam; Taimoor, Alruba; Nazir, Aamir; Zaman, Uzma; Azmat, Saania; Nawaz, Farhat (Journal of Ayub Medical College Abbottabad, 2021)
Background: One of the frequent obstetric complications in first trimester is vaginal bleeding. It has an incidence of 16%-25%. Subchorionic haemorrhage is the most common cause of first trimester miscarriage associated with vaginal bleeding. The objective of the study was to determine the association of subchorionic hematoma (SCH) with preterm labour in pregnant females with threatened abortion. Methods: A Cohort Study was designed and conducted in the Obstetrics and Gynaecology Department, Zanana hospital, Dera Ismail Khan (D.I. Khan). A sample size of 418 subjects was equally divided into two equal groups. Non-probability consecutive sampling was used for collection of samples. Pregnant women presenting with sub chorionic hematoma were considered as cases while pregnant women without sub chorionic hematoma were considered as controls. The diagnosis of sub chorionic haemorrhage was established by ultrasound. Data was analysed by SPSS version 22.0 for description, i.e., frequencies and percentages were calculated for categorical variables and for continuous variables, mean±standard deviation (±SD) was calculated. To compare preterm labour in both groups Chi-square test was applied and p‰¤0.05 was taken as significant. Stratification was done with regard to age, gestational age, parity, history of hypertension, and weight to see the effect of these variables on preterm labour. Chi-square test was used for post stratification for both groups and p ‰¤ 0.05 was considered statistically significant and relative risk was calculated. Results: The age range was from 18-40 years in group A with a mean age of 29.08±2.88 years while it was 28.41±2.94 years in group B. Mean gestational age was 13.99±3.15 weeks in group A and 11.42±3.37 weeks in group B. Mean parity was 0.91±1.14 in group A and 0.78±1.09 in group B respectively. Mean weight of subjects in group A was 68.31±10.27 and 67.55±10.09 Kg in group B. Majority of the patients were of 18-30 years in both groups (group A; 78.5% and group B; 78.9%). History of hypertension was noted in 33% in group A and 12.9% in group B. In group A, preterm labour was seen in 40 (19.1%) patients as compared to 61 (29.2%) patients in group B, (p=0.02, R.R=0.65). Conclusion: Subchorionic hematoma in patients with threatened abortion during the first half of the pregnancy may not increase the risk of preterm labour.